Modern Jewish philosophy and the politics of divine violence - Weiss, Daniel H. (Cambridge University Press, 2023)
Is commitment to God compatible with modern citizenship? In this book, Daniel H. Weiss provides new readings of four modern Jewish philosophers - Moses Mendelssohn, Hermann Cohen, Franz Rosenzweig, and Walter Benjamin - in light of classical rabbinic accounts of God's sovereignty, divine and human violence, and the embodied human being as the image of God. He demonstrates how classical rabbinic literature is relevant to contemporary political and philosophical debates. Weiss brings to light striking political aspects of the writings of the modern Jewish philosophers, who have often been understood as non-political. In addition, he shows how the four modern thinkers are more radical and more shaped by Jewish tradition than has previously been thought. Taken as a whole, Weiss' book argues for a fundamental rethinking of the relationship between Judaism and politics, the history of Jewish thought, and the ethical and political dynamics of the broader Western philosophical tradition.